ANALYSIS OF COMPOSITE RESTORATIONS IN PATIENTS BELOW 21 YEARS OF AGE - A RETROSPECTIVE STUDY - Packyanathan, Jerusha Santa; K, Sowmya (International Journal of Psychosocial Rehabilitation, 2019)
Caries is still quite prevalent, despite great measures taken to curb its incidence. Identifying the decay early and restoring them can have favourable prognosis and long term benefits. Addressing the caries early means treatment with less invasive treatment modalities by means of a restoration. The aim of this study was to analyze the number, gender and teeth distribution of composite restorations in patients below 21 years of age. This was a retrospective study conducted by evaluating data of patients below 21 years of age visiting a private dental college between June 2019 to March 2020. The following data were retrieved from the dental records: patient age, gender, tooth type with restoration and arch involved was analysed.The coding was done in MS excel. The data was transferred to a host computer and processed using SPSS software version 20.0 (SPSS Inc., Chicago, IL, USA) by tabulation and graphical illustration. Descriptive statistics was used to study the data collected and to analyse frequency and percentage distribution. Chi square test was used to assess association at 5% significance level (P< 0.05). The results showed that the permanent dentition age group (13-21 years) had a higher number of composite restorations than mixed dentition age group (6-12 years). Males had a higher number of restorations when compared to females. The molar teeth and mandibular arch had the maximum number of composite restorations. Our study also showed that the association between age, gender and arch with type of tooth restored with composite to be highly significant (P value- 0.000).